Integration of Transcriptomics and Metabolomics for Understanding the Different Vegetative Growth in Morchella Sextelata - Deng, Kejun; Lan, Xiuhua; Chen, Ying; Wang, Ting; Li, Mengke; Xu, Yingyin; Cao, Xuelian; Xie, Guangbo; Xie, Liyuan (Frontiers in Genetics, 2022)
Morchella sextelata is an edible and medicinal fungus with high nutritional, medicinal, and economic value. Recently, M. sextelata has been produced through artificial cultivation in China, but its stable production remains problematic because the details of its growth and development process are limitedly understood. Herein, to investigate the dynamic process of M. sextelata development, we integrated the transcriptomics and metabolomics data of M. sextelata from three developmental stages: the young mushroom period (YMP), marketable mature period (MMP), and physiological maturity period (PMP). The results showed that the transcriptome changed dynamically at different stages and demonstrated the significant enrichment of pathways that regulate plant growth and development, such as N-glycan biosynthesis and carbon and purine metabolism. Similarly, small-molecule metabolites, such as D-fructose-1,6-biphosphate, which was upregulated during the YMP, dihydromyricetin, which was upregulated during the MMP, and L-citrulline, which was upregulated during the PMP, also showed phase-dependent characteristics. Then, combined analysis of the transcriptome data and metabolome traits revealed that the transcriptome may affect metabolic molecules during different growth stages of M. sextelata via specific enzymes, such as α-glucosidase and glucanase, which were included in two opposite transcriptome modules. In summary, this integration of transcriptomics and metabolomics data for understanding the vegetative growth of M. sextelata during different developmental stages implicated several key genes, metabolites, and pathways involved in the vegetative growth. We believe that these findings will provide comprehensive insights into the dynamic process of growth and development in M. sextelata and new clues for optimizing the methods for its cultivation application.